Endodontic Retreatment of a Maxillary Central Incisor with Two Root Canals in a Patient with Cleft Lip and Palate - Candeiro, George Taccio Miranda; Viana, Francisca Livia Parente; Paiva, Hermano Camelo; Caldeira, Celso Luis; Iglecias, Elaine Faga; Gavini, Giulio (Iranian Endodontic Journal, 2019)
The failures in endodontic treatments are often related to anatomical variations. Some anatomical changes in anterior teeth occur in patients with cleft lip and palate. This paper aims to report the endodontic retreatment of a maxillary central incisor with two roots and two canals on a patient who presents cleft lip and palate. A male patient, 11-year-old, reported pain when chewing related to the left maxillary central incisor tooth (tooth 21) which featured a sinus tract after primary endodontic treatment. In periapical radiograph, it was observed an alteration on the anatomy of the root on the tooth 21, which featured a radiolucent area on the dental apex and had been properly endodontically treated. In cone-beam computed tomography (CBCT) images the presence of an accessory root in the palatal region was observed, that had not been prepared, or filled. Thus, the non-treated accessory canal was instrumented with the crown-down technique and filled with gutta-percha and endodontic sealer. After 1 year of follow-up, the patient presented the tooth with a normal masticatory function and no painful symptoms. Therefore, it can be concluded that the additional root canals may be present and the CBCT is an important tool to evaluate the internal root morphology. In cleft lip and palate patients, the root canals morphology should be carefully analyzed due to high prevalence of dental anomalies which may influence the success in endodontic treatment. Keywords: Cleft Lip-palate; Cone-Beam Computed Tomography; Dental Anatomy; Endodontic Retreatment; Maxillary Central Incisor